Batik Indonesia MSMEs in the Digital Era: Innovating Tradition, Overcoming COVID-19 - Steelyana Wiyarti, Evy (APPS Publications, 2025)
The COVID-19 pandemic has profoundly impacted Batik’s Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in regions such as Sumenep, Yogyakarta, Lasem, Solo, and Pekalongan. This paper examines the common challenges faced by these enterprises, including a significant decline in sales due to tourism closures, supply chain disruptions leading to increased raw material costs, and financial instability characterized by liquidity crises and salary deferrals. In response, various regional strategic adaptations have emerged, with MSMEs leveraging digital platforms like WhatsApp and Instagram for sales, while others have piloted e-commerce initiatives despite facing technical skill gaps. Government interventions, including subsidies for digital infrastructure and facilitation of SNI certification, have aimed to bolster the resilience of these enterprises. The findings reveal that while the pandemic accelerated digital adoption, it also exposed systemic gaps such as inequitable access to online tools and skill deficits among MSMEs. The reliance on pre-existing community networks has proven crucial for resilience, particularly in Solo, where social capital has facilitated bulk orders and community support. Contrary to traditional economic theories emphasizing price elasticity, the survival of these enterprises has hinged more on non-monetary strategies, such as customer engagement through social media. In conclusion, while Batik MSMEs have demonstrated remarkable adaptability, structured support is essential for their continued recovery and growth. Recommendations include expanding digital infrastructure training, providing tailored financial aid, and integrating cultural preservation into national tourism recovery plans. Future research should explore the longitudinal impacts of digital transformation on cultural authenticity within the MSME sector, contributing to a more comprehensive understanding of the interplay between economic resilience and cultural heritage in the face of global challenges.